The Role of Bhabhinkamtibmas in Combating Crimes Committed by Youth Through Coffee Farming Empowerment (Case Study of Girimulyo Kulon Progo Research) - Suranto, Suranto; Laksana, Andri Winjaya (UNISSULA Semarang, 2025)
This study aims to determine and analyze the role of Bhabinkamtibmas in the context of overcoming criminal acts committed by young people through empowering coffee farming in the Purwosari area, Kapanewon Girimulyo Kulon Progo in order to prevent criminal acts, and the obstacles encountered by Bhabinkamtibmas in the context of overcoming criminal acts committed by young people through empowering coffee farming, as well as solutions in anticipating the obstacles encountered. This research approach is carried out using sociological juridical, namely identifying and conceptualizing law as a real and functional social institution in a real life system, after primary and secondary data are obtained, a qualitative analysis is carried out, namely a material analysis method by describing the data obtained in the form of detailed and clear sentences, using deductive and inductive thinking methods. The results of the study can be concluded that the role of Bhabinkamtibmas in the context of overcoming criminal acts committed by young people through empowering Coffee Farming is carried out in two ways, namely first identifying the background of the problem related to the importance of carrying out agricultural empowerment, Second implementing the results of the identification that has been formulated by preventing criminal acts through a social approach, the lack of employment opportunities and skills possessed by young people, carrying out mentoring efforts to encourage becoming entrepreneurs who are closer to the digital market and becoming a facilitator with competent stakeholders. Obstacles encountered are lack of technical knowledge, lack of resources and facilities, lack of community participation, weather and environmental constraints, climate change, pests, and plant diseases that can affect crop yields, coordination with related agencies, and the private sector. budget limitations. Solutions in overcoming obstacles in changing mindsets by showing that coffee farming can be a profitable business holding interesting training and workshops, such as barista techniques, coffee roasting, and digital marketing, by promoting the success stories of young coffee farmers as inspiration, Encouraging business capital assistance programs or people's business credit (KUR) specifically for young farmers. Proposing a land rental program from senior farmers to young people to start farming, Encouraging cooperation between young people in the form of cooperatives or agribusiness communities, Holding coffee cultivation training from upstream to downstream by involving agricultural experts and coffee industry players, providing internship programs on coffee plantations or coffee processing industries.